GUIDELINES FOR STOCK MANAGEMENT IN PRIVATE HOSPITALS - Sritiraj , Terawat; Phon-ngam, Patthira (Journal of MCU Nakhondhat, 2023)
This academic paper aims to study the warehouse management approach in private hospitals. A study method by searching for information from various academic papers and articles about warehouse concept, how to manage your warehouse for maximum efficiency, warehouse management process, strategies for storing products in the warehouse. Data analysis by Scott’s approach selected relevant documents based on 1) validity, 2) reliability, 3) representation, and 4) clarity, using document interpretation and factual data synthesis various. The study found that the most efficient warehouse management must do as follows 1) keep the area tidy by drawing up a warehouse plan, 2) labeling in the warehouse, the position for stock must be labeled and clearly labeled, and 3) the equipment in the warehouse must be of the highest quality in the warehouse. The guidelines for warehouse management in private hospitals are as follows: 1) area management by managing the warehouse area to be tidy 2) receiving system must classify products and export products. by receiving the goods, which are raw materials in the production process, into the warehouse system according to the order 3) use mobile network system by allowing specific users or related persons to be able to communicate, transmit data, connect between various devices used in the warehouse by using wireless technology, such as portable barcode readers 4) use electronic program packages by developing a packaged program that can control the receipt of goods 5) the visual control system is a visual operation control system and 6) manage the warehouse control personnel by training the dispensing and recording staff. There will be a schedule. training within the department